Implementasi Business Intelligence untuk Menganalisis Data Tujuan Populer Untuk Bali Tahun 2022 menggunakan Aplikasi Tableau Public - Ahmad Syahril; E Erizal; Firman Noor Hasan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The most important part in a business is data management, it's just that the steps are not easy. In the development of technology, there are many ways to process and manage data. Business intelligence (BI) may be one of them. Maybe according to estimates the tourist attractions in Bali are the world's top tourist attractions. TripAdvisor named Bali as the world's top destination in the Traveler's Choice award. According to Google Reviewrs, tours in Bali show the highest number of 4,800 and the lowest 4,200. Providing highly effective information is the goal of tourism research in Bali, Indonesia, which is based on business intelligence. For this study, data analysis was performed using Tableau Public software. In Google Reviews, Bali Safari and Marine Park has the highest score with 16,042 and Banjar Hot Spring has the lowest score with 2,422. According to Google Maps, the highest rating rating in Bali is the Penglipuran Village area, with a value of 4,800 and the lowest rating is occupied by an area called Goa Gajah with a value of 4,200.